Long‐term outcomes of liver transplantation for hepatoblastoma: A single‐center 14‐year experience. (11th June 2018) - Ramos‐Gonzalez, Gabriel; LaQuaglia, Michael; O'Neill, Allison F.; Elisofon, Scott; Zurakowski, David; Kim, Heung Bae; Vakili, Khashayar
Abstract: HB is the most common primary liver tumor in children. Complete tumor excision, either by partial resection or by total hepatectomy and liver transplantation, in combination with chemotherapy provides the best chance for cure. We performed a retrospective analysis of patients who underwent liver transplantation for HB and herein present our 14‐year single‐institution experience. Twenty‐five patients underwent liver transplantation for HB at a median age of 26 months (IQR: 15‐44). Graft survival was 96%, 87%, and 80% at 1, 3, and 5 years, respectively. There were four patient deaths, three of them due to disease recurrence within the first year post‐transplant. Ten‐year overall survival was 84%. Three recipients initially presented with pulmonary metastases and underwent resection of metastatic disease, of which two are alive at 3.9 years. Of three patients who underwent salvage transplants, two are alive at 1.5 years after transplant. Non‐survivors were associated with lower median alpha fetoprotein value at presentation compared to survivors (21 707 vs 343 214; P  = .04). In conclusion, the overall long‐term outcome of primary liver transplantation for HB is excellent. Tumor recurrence was the highest contributor to mortality. Even patients with completely treated pulmonary metastases prior to transplant demonstrated a favorable survival.